1995
DOI: 10.1021/bi00036a025
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Steroid Sulfatase by an Active Site-Directed Inhibitor, Estrone-3-O-Sulfamate

Abstract: Steroid sulfatases are responsible for the hydrolysis of 3beta-hydroxy steroid sulfates, such as cholesterol and pregnenolone sulfate, and have an important role in regulating the synthesis of estrogenic steroids, from estrone sulfate and dehydroepiandrosterone sulfate, in endocrine-dependent tumors. Although little is known about the mechanism by which the sulfate group is removed from a steroid nucleus, an active site-directed sulfatase inhibitor has been developed. This inhibitor, estrone-3-O-sulfamate (EMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 162 publications
(132 citation statements)
references
References 20 publications
5
126
0
1
Order By: Relevance
“…However, recent finding indicated that the third ring appears to be predominately in the boat conformation rather than previously proposed chair conformation based on temperature factors (B-factors) and electron density map results [79]. With the advent of this new finding regarding the conformation of the 7-membered ring on compound 30 it can now be explained that its higher potency (IC 50 value of 8 nM and K i value of 40 nM) than EMATE (IC 50 = 25 nM and K i = 670 nM) is attributed to the tendency to mimic the steroidal CD-ring; perhaps, better hydrophobic interactions due to favorable binding to the active site of the enzyme are in play [61,85,86].…”
Section: Sulfatase Inhibitormentioning
confidence: 99%
“…However, recent finding indicated that the third ring appears to be predominately in the boat conformation rather than previously proposed chair conformation based on temperature factors (B-factors) and electron density map results [79]. With the advent of this new finding regarding the conformation of the 7-membered ring on compound 30 it can now be explained that its higher potency (IC 50 value of 8 nM and K i value of 40 nM) than EMATE (IC 50 = 25 nM and K i = 670 nM) is attributed to the tendency to mimic the steroidal CD-ring; perhaps, better hydrophobic interactions due to favorable binding to the active site of the enzyme are in play [61,85,86].…”
Section: Sulfatase Inhibitormentioning
confidence: 99%
“…Potent inhibitors such as 17a-t-butylbenzyl-E 2 , 20 estrone sulfamate (EMATE) 10,11 and 17a-t-butylbenzyl-EMATE 22 were also used as reference compounds. The experimental conditions for measuring IC 50 were the same as in the screening assay, except that a range of inhibitor concentrations was used and two substrates studied; [ 3 H]-labeled E 1 S (100 mM) and […”
Section: Ic 50 Valuesmentioning
confidence: 99%
“…11,12 Unexpectedly, EMATE proved to be a potent estrogen on oral application in the rat. 13 This is thought to result from its absorption into red blood cells after ingestion thus protecting it from inactivation during transit through the liver.…”
mentioning
confidence: 99%